2010
DOI: 10.1007/s11596-010-0560-z
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the sonic hedgehog signalling pathway inhibits choroidal neovascularization in a laser-induced rat model

Abstract: Sonic hedgehog (Shh) signaling has recently been shown to be involved in the pathological angiogenesis in response to tissue hypoxia and ischemic injury. Hypoxia/ischemia is considered to play an important role in the development of choroidal neovascularization (CNV). This study was aimed to examine the effect of blockade of the Shh signaling pathway on CNV and the underlying mechanism. A total of 64 male Brown-Norway (BN) rats were used in this study. One eye of each rat underwent laser photocoagulation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…We have utilized the intravitreal administration of YC-1 as a method of drug delivery, because this route delivers the drug in close proximity to the localization of the pathology, while the vitreous serves as a drug reservoir, which keeps the drug longer at the site. In addition, the sextuple injection regimen, which implemented in this study, was used to maximize chances of success for proof of concept, but is not ideal for clinical application, despite that implementing the same modality (multiple intravitreal injections) have been previously reported in various investigations [37] , [38] , [39] , [40] , [41] . The selection criterion of sextuple injection regimen was based on the standards, which we have established throughout our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…We have utilized the intravitreal administration of YC-1 as a method of drug delivery, because this route delivers the drug in close proximity to the localization of the pathology, while the vitreous serves as a drug reservoir, which keeps the drug longer at the site. In addition, the sextuple injection regimen, which implemented in this study, was used to maximize chances of success for proof of concept, but is not ideal for clinical application, despite that implementing the same modality (multiple intravitreal injections) have been previously reported in various investigations [37] , [38] , [39] , [40] , [41] . The selection criterion of sextuple injection regimen was based on the standards, which we have established throughout our previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is associated with increased Gli1 and Vegfa expression levels [103]. In addition, Shh and Ptch1 are overexpressed in the eye both in retinopathy of prematurity (ROP) [47] and in laser-induced choroidal neovascularization [47,104], promoting pathological angiogenesis; inhibition of the Hh pathway (Cyclopamine) results in reduced angiogenesis and decreased Vegfa and Ptch1 levels, placing Shh activation upstream of Vegfa in experimental retinal angiogenesis [47]. Moreover, in mice with chronic liver injury or mice that underwent acute partial hepatectomy, administration of a Smo antagonist (GDC-0449 or Cyclopamine) prevents liver sinusoidal EC capillarization [105], and a study suggests that Annexin a2 may promote EC proliferation and angiogenesis by increasing Ihh and Gli1 in the setting of rheumatoid arthritis [106].…”
Section: Postnatal Angiogenesismentioning
confidence: 99%
“…SHH signaling has recently been shown to be involved in pathological angiogenesis in response to tissue hypoxia and ischemic injury. It was concluded that the SHH inhibitor cyclopamine can effectively inhibit the development of laser-induced experimental choroidal neovascularization 59 . In addition, whole-exome sequencing and Sanger sequencing con rmed that Shh was differentially expressed and was one of the potential pathogenic mutations in peripheral venous blood samples of glaucoma patients compared with those of the ethnicity-matched normal control group.…”
Section: Discussionmentioning
confidence: 99%